PERBANDINGAN KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI INDONESIA DENGAN LEMBAGA PEMBERANTASAN TINDAK PIDANA KORUPSI NEGARA SINGAPURA, HONG KONG, DAN MALAYSIA - Rhendra Kusuma (University Of Bengkulu Law Journal, 2022)
The Corruption Eradication Commission (KPK) of the Republic of Indonesia is one of the pioneers on corruption practices combat in Indonesia. KPK is well known for its achievements in criminal acts of corruption in Indonesia, even though the regulations that discuss the Corruption Eradication Commission often becoming a debatable material by legal experts in Indonesia. The answer to this question can be done by conducting a comparative legal study. This comparative legal study was conducted to compare the corruption eradication system in Indonesia with corruption eradication agencies in other countries to find out what are the similarities and differences. This writing aims to see and analyze the similarities and differences between the Indonesian Corruption Eradication Commission with the Corrupt Practices Investigation Bureau Singapura, Independent Commission Against Corruption Hongkong and Suruhanjaya Pencegahan Rasuah Malaysia/ Malaysian Anti-Corruption Commission.